Pemahaman Konsep Siswa melalui Model Inkuiri Terbimbing Berbantuan Simulasi PhET - Asep Abdur Rais; Lukman Hakim; Sulistiawati Sulistiawati (Faculty of Science and Education, UIN Walisongo Semarang, 2020)
The purpose of this study is to understand students' concepts on indicators exemplifying the level of understanding of student concepts through guided inquiry. The population of this study was all grade XI students in one of the high schools in Palembang. This research is quantitative research. The results of understanding students' concepts can be seen from the results of the posttest of each class using t-test. Based on the results of the study showed there were differences between students in the experimental class and the control class. This can be seen from the t-test using SPSS 22 obtained significant results (2 –tailled of 0.00. These results indicate the guided inquiry model has an influence on understanding the concepts of physics.